2003
DOI: 10.1021/jf0261405
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Isoflavone of Soybean Cultivars with Location and Storage Duration

Abstract: Fifteen soybean [Glycine max (L.) Merrill] cultivars were grown in Seoul, Suwon, and Kyongsan, Korea, in 1998, 1999, and 2000, and their isoflavone contents were assessed. After harvest, the beans were stored for 3 years at room temperature. Soybean isoflavones were analyzed using high-performance liquid chromatography (HPLC) within each crop year and after storage. Total isoflavone contents ranged from 188.4 to 685.6 mg 100 g(-1) in 1998, from 218.8 to 948.9 mg 100 g(-1) in 1999, and from 293.1 to 483.0 mg 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
93
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 22 publications
19
93
2
3
Order By: Relevance
“…A ausência de acetilglicosídeos está justificada uma vez que sua formação está associada a processamentos envolvendo calor seco, como a tostagem e a extrusão da farinha de soja (COWARD et al, 1998). Por outro lado, a formação de agliconas resulta da atuação das β-glicosidases endógenas, como, por exemplo, quando a soja é deixada de molho ou mesmo durante armazenamento prolongado em condições de alta umidade relativa (MATSUURA et al, 1989;LEE et al, 2003). Isso explica a baixa porcentagem presente nas sementes, cuja formação foi provavelmente decorrente do processo de moagem e extração da soja para a análise.…”
Section: Resultsunclassified
“…A ausência de acetilglicosídeos está justificada uma vez que sua formação está associada a processamentos envolvendo calor seco, como a tostagem e a extrusão da farinha de soja (COWARD et al, 1998). Por outro lado, a formação de agliconas resulta da atuação das β-glicosidases endógenas, como, por exemplo, quando a soja é deixada de molho ou mesmo durante armazenamento prolongado em condições de alta umidade relativa (MATSUURA et al, 1989;LEE et al, 2003). Isso explica a baixa porcentagem presente nas sementes, cuja formação foi provavelmente decorrente do processo de moagem e extração da soja para a análise.…”
Section: Resultsunclassified
“…Isoflavone contents of soy products are presented in Table 2 and representative HPLC chromatograms in Figure 1 (except for that of soy seeds presenting the same content of the raw whole soybean flour). Total isoflavone content varied among different soy varieties and environmental growing conditions (Wang and Murphy, 1994;Lee et al, 2003) and the Ecuadorian variety (~ 68 mg per 100 g) was found in the same range of Brazilian varieties, from 57 to 188 mg per 100 g of soybeans (Genovese et al, 2005) and could be considered low when compared to American (116 to 274 mg/100 g) and Korean varieties (188 to 949 mg/100 g) (Wang et al, 2000;Lee et al, 2003). The soy products represent a way of incorporating isoflavones in the diet of populations that do not consume the grains.…”
Section: Hplc Quantitation Of Isoflavonesmentioning
confidence: 99%
“…These levels were much higher than those reported by Wang et al [18] or Coward et al [19], who found malonylglucoside, glucoside, acetylglucoside and aglycone levels to be 1,013 and 1,340 µg/g, 475 and 249 µg/g, 0 and 207 µg/g, and 24 and 11 µg/g, respectively. These differences may be accounted for by variations in cultivar, growth environment, harvest time and storage conditions [6,20]. …”
Section: Isoflavone Content In Soybean Cakementioning
confidence: 99%
“…By comparing maltodextrin concentrations of 20 % were also compared and the optimum level was found to be 20 %. By controlling the inlet temperature at 180 °C and outlet temperature at 120 °C, a total amount of 7.9 g powder (6.1% H 2 O) containing 1,887 µg/g isoflavone was obtained after spray drying.…”
Section: Processing Of Isoflavone Powder By Spray Dryingmentioning
confidence: 99%